KARAKTERISTIK TREN BUSANA MUSLIMAH GEN Z DI LINGKUNGAN MAHASISWI UMSIDA UNTUK MEMBANTU SEGMENTASI UMKM FASHION MUSLIM - Ningsih, Diah Krisna (WELFARE: Journal of Islamic Economics and Finance, 2024)
This research aims to identify Muslim fashion trends among Generation Z to support the segmentation of Muslim fashion products for MSMEs in Sidoarjo. The easiest environment to find the Gen Z community is the educational setting, such as Muhammadiyah University of Sidoarjo (UMSIDA). This generation, born after 2000, is capable of making independent consumption decisions based on personal needs and desires. Therefore, students represent a potential market for MSME product segmentation.           This study employs a descriptive quantitative method to determine the value of independent variables using numerical data. The variables examined include respondents' interests and clothing styles, as well as their consumption behavior for fashion products. Secondary data is derived from theories of fashion and style, Muslim clothing theory, and fashion aesthetics theory. Data collection was carried out by distributing questionnaires (via Google Forms) to 139 UMSIDA female students born between 2000 and 2006 (aged 19-24).          The findings indicate that the most preferred clothing style among UMSIDA female students is formal attire for college or work, favored by 74.8%, while the remainder prefer non-formal styles. The dominant styles are Feminine-Casual and Feminine-Classic. The Feminine-Casual style reflects a strong female character that is girly, soft, calm, yet energetic, with simple elements such as pastel colors and minimal modifications or details. Meanwhile, the Feminine-Classic style reflects a stronger character than casual, characterized by girly, soft, calm, and consistent traits, with less inclination to follow trends. Key words:Muslim Fashion Trends, Consumer Behavior, Gen Z, UMSIDA Students